The prognostic value of angiography-based vessel fractional flow reserve after percutaneous coronary intervention: The FAST Outcome study. (15th July 2022) - Neleman, Tara; Scoccia, Alessandra; Masdjedi, Kaneshka; Tomaniak, Mariusz; Ligthart, Jurgen M.R.; Witberg, Karen T.; Vermaire, Alise; Wolff, Quinten; Visser, Leon; Cummins, Paul; Kardys, Isabella; Wilschut, Jeroen; et al.
Abstract: Background: Vessel Fractional Flow Reserve (vFFR) as assessed by three-dimensional quantitative coronary angiography has high correlation with pressure wire-based fractional flow reserve in both a pre- and post-PCI setting. The present study aims to assess the prognostic value of post-PCI vFFR on the incidence of target vessel failure (TVF), a composite endpoint of cardiac death, target vessel myocardial infarction and target vessel revascularization (TVR) at 5-year follow up. Methods: Post-PCI vFFR was calculated after routine PCI in a total of 748 patients (832 vessels) with available orthogonal angiographic projections of the stented segment. Results: Median age was 65 (IQR 55–74) years, 18.2% were diabetic, and 29.1% presented with stable angina. Median post-PCI vFFR was 0.91 (IQR 0.86–0.95). Vessels were categorized into tertiles based on post-PCI vFFR: low (vFFR <0.88), middle (vFFR 0.88–0.93), and upper (vFFR ≥0.94). Vessels in the lower and middle tertile were more often LADs and had smaller stent diameters ( p <0.001). Vessels in the lower and middle tertile had a higher risk of TVF as compared to vessels in the upper tertile (24.6% and 21.5% vs. 17.1%; adjusted HR 1.84 (95%CI 1.15–2.95), p  = 0.011, and 1.58 (95%CI 1.02–2.45), p  = 0.040) at 5-years follow-up. Additionally, vessels in the lower tertile had higher rates of TVR as compared to vessels in the higher tertile (12.6% vs. 6.5%, adjusted HR 1.93 (95%CI 1.06–3.53), p  = 0.033). Conclusion: Lower post-PCI vFFR values are associated with a significantly increased risk of TVF and TVR at 5-years follow-up. Highlights: Suboptimal post-PCI FFR is related to an increased risk of cardiovascular events. vFFR, an angiography-derived FFR index, correlates strongly with invasive FFR. Lower post-PCI vFFR values were found more often in LAD vessels and smaller stents. Lower post-PCI vFFR values had higher rates of target vessel failure at 5-years. Post-PCI vFFR might identify those who require additional post-PCI optimization.